Emotion Display Rules, Emotion Regulation, and Teacher Burnout - Chang, Mei-Lin (Frontiers in Education, 2020)
Cognitive appraisal theories of emotions suggest that emotions are elicited by evaluations of events and situations and that our beliefs influence the ways we appraise or judge situations that we encounter. Gross and John (2003) theorized cognitive reappraisal and expressive suppression as two general forms to regulate emotions. Although teacher emotion has been studied more extensively in the recent decade, Chang (2009b) has argued that there is a need for research into the ways that teachers’ implicit beliefs and cognitive processes influence their emotional reactions to the sources of burnout. Particularly, how emotional display rules serve as underlying principles that guide teachers to make decisions either consciously or unconsciously to express or not to express emotions. This study aims to examine the relationships among teachers’ beliefs about emotional display rules in the classroom, and the approaches in emotion regulation, and the subsequent feelings of burnout. Survey data was collected from 561 full-time teachers and subjected to hypothesis testing using structural equation modeling. The model provides evidence supporting a pathway between emotion display rules and expressive suppression. These display rules are particularly influential to expressive suppression which also leads to all three dimensions of burnout: emotional exhaustion, depersonalization, and reduced personal accomplishment. Further, uses of cognitive reappraisals are found negatively associated with teacher burnout in all three dimensions. Results of the study indicated that teacher education or profession development should be designed to help teachers to detect and reframe their beliefs about display rules and to engage in cognitive reappraisal so that they may effectively manage their day-to-day emotions in the classroom.